Zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst and its preparation method and application

By adopting silicon molecules in traditional precious metal catalysts to seal platinum nano -particle catalyst, the traditional catalysts are prone to loss and stability under high temperature conditions. Important industrial application value.

CN116422367BActive Publication Date: 2025-01-28TIANJIN NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310225846.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-01-28
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

Traditional supported precious metal catalysts have problems such as easy loss of metal active species, poor thermal stability and low catalytic efficiency, especially under high temperature conditions, resulting in a sharp decline in catalytic performance.

Method used

Use a silicon molecules to seal the platinum nano-nanoparticles catalyst (PT@ZR-MFI), synthesize the PT nano-particle particles through the molecular sieve holes, and improve the catalytic activity and utilization rate of precious metal PT, and enhance the PT sub-Asia through the rigid structure of the molecular sieve skeleton skeleton. The stability of nanoparticles.

Benefits of technology

Realized the efficient hydrogenation performance of catalysts and advanced LEWIS acidity. In the reaction of acetyl propadic acid and organic amine, it shows excellent catalytic activity and the yield of N-replacement-5-methalphenone. The catalyst structure is stable. After multiple cycles, the catalytic activity has not decreased, the preparation process is simple, the catalytic performance is excellent, the cost is low and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst and a preparation method thereof. The chemical expression of the catalyst is Pt@Zr-MFI, wherein the Zr-MFI is a zirconium-containing zeolite molecular sieve having MFI topological structural characteristics, and the Pt is a platinum sub-nano particle confined in the pores of the Zr-MFI molecular sieve. The Pt@Zr-MFI catalyst provided by the present invention has both excellent catalytic hydrogenation performance and advanced Lewis acidity. In the application of preparing N-substituted-5-methylpyrrolidone with levulinic acid and organic amine as raw materials, it shows excellent catalytic activity and N-substituted-5-methylpyrrolidone yield, the catalyst structure is stable, and its catalytic activity does not show a significant decrease after repeated use. The catalyst preparation process is simple, the catalytic performance is excellent, the catalytic process is low-cost and green and environmentally friendly, and it has important industrial application value in the field of pyrrolidone preparation technology.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention application was supported by the National Natural Science Foundation of China Youth Fund Project (Project No.: 22002108). Technical Field

[0002] The invention belongs to the technical field of pyrrolidone catalysts, and specifically relates to a catalyst for preparing N-substituted-5-methylpyrrolidone from levulinic acid and an organic amine, and a preparation method and application thereof. Background Art

[0003] As global warming, energy crisis and other issues continue to intensify, it is urgent to develop renewable, clean, high-value-added chemicals and energy supply systems that do not rely on fossil resources. Levulinic acid is one of the 12 most important biomass platform molecules identified by the U.S. Department of Energy. It is mainly derived from the hydrolysis products of cellulose and hemicellulose, which can be further converted to prepare high-value-added biomass-based downstream products. Among them, the chemical conversion process of levulinic acid into the organic functional compound pyrrolidone (and its N-substituted derivatives) has attracted widespread attention from scientific researchers (M. Sajid, U. Farooq, G.Bary, M. Azim, X. Zhao, Green Chem .,2021, 23 , 9198~9238). Pyrrolidone (and its N-substituted derivatives) are an important class of nitrogen-containing compounds. They can be used as solvents, surfactants, pharmaceutical intermediates, pesticide active ingredients, and fuel additives in industry, and have broad application prospects (J. Vidal, M. Climent, P. Concepcíon, A. Corma, S.Iborra, M. Sabater, ACS Catal. ,2015, 5 , 5812~5821).

[0004] The reductive amination of levulinic acid with hydrogen as a reducing agent in the presence of a hydrogenation catalyst is considered to be the most economical and green synthetic route for the synthesis of pyrrolidone compounds (J. He, L. Chen, S. Liu, K. Song, S. Yang, A. Riisager, Green Chem .,2020, 22 , 6714~6747;Xue, D. Yu, X. Zhao, T. Mu, Green Chem .,2019, 21 , 5449~5468; L. Yan, Q. Yao, Y. Fu, Green Chem .2017, 19, 5527~5547). Compared with the homogeneous catalytic process, the nanoparticle heterogeneous catalytic system represented by precious metals (Ru, Rh, Pt and Pd) and non-precious metals (Cu, Ni, Co and Fe) has more industrial application value (L.Manzer, US 6743819 B1, 2004; L.Manzer, US 7465813 B2, 2008; J. Vidal, M. Climent, P. Concepcíon, A. Corma, S. Iborra, M. Sabater, ACS Catal. ,2015, 5 , 5812~5821; G. Gao, P. Sun, Y. Li, F. Wang, Z. Zhao, Y. Qin, F. Li, ACS Catal .,2017, 7 , 4927~4935; A. Touchy, S.Siddiki, K. Kon, K. Shimizu, ACS Catal .,2014, 4 , 3045~3050; J. Zhang, B. Xie, L. Wang, X. Yi, C. Wang, Z. Dai, A. Zheng, F. Xiao, ChemCatChem ,2017, 9 , 2661~2667). However, traditional supported metal catalysts generally have poor stability, and metal active species are easily lost during the reaction process. Under high temperature conditions, the migration of metal nanoparticles can easily cause serious aggregation problems, and changes in surface structure and properties lead to a sharp decline in catalytic performance. In addition, precious metal resources are scarce and expensive. How to improve the utilization efficiency of precious metals and thus reduce the amount of precious metals loaded in catalysts to reduce synthesis costs is also an important consideration in its industrialization process. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst, which has both excellent hydrogenation performance and advanced Lewis acidity.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst.

[0007] Another object of the present invention is to provide the use of the above-mentioned zirconium silicate molecular sieve encapsulated platinum sub-nano particle catalyst in the preparation of N-substituted-5-methylpyrrolidone using levulinic acid and organic amine as raw materials, and the catalyst exhibits excellent catalytic activity and N-substituted-5-methylpyrrolidone yield.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] The chemical expression of the zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst provided by the present invention is Pt@Zr-MFI, wherein the Zr-MFI is a zirconium-containing zeolite molecular sieve with MFI topological structure characteristics, and the Pt is a platinum sub-nano particle.

[0010] @ represents that Pt is confined in the pores of Zr-MFI molecular sieve.

[0011] The preparation method of the catalyst of zirconium silicon molecular sieve encapsulating platinum sub-nano particles provided by the present invention comprises the following steps:

[0012] 1) At room temperature of 20-25 °C, add a certain amount of imidazole ionic liquid and distilled water into a beaker, stir until the solution is clear, and then add potassium tetrachloroplatinate to the above solution for 1-2 h to obtain a Pt precursor solution;

[0013] 2) Tetraethyl orthosilicate, metal zirconium salt and distilled water are mixed evenly, and tetrapropylammonium hydroxide solution is slowly added under stirring. After continuous stirring for 2 to 4 hours, the Pt precursor solution prepared in step 1) is added to the above sol. After the Pt precursor solution is completely mixed, the sol is transferred to a hydrothermal synthesis reactor, crystallized at 140 to 170 °C for 3 to 7 days, filtered, washed and dried to obtain a solid powder;

[0014] In the above steps, the imidazole ionic liquid is 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide or 1-butyl-3-methylimidazolium bromide;

[0015] The metal zirconium salt is zirconium tetrachloride, zirconium oxychloride octahydrate or zirconium oxynitrate;

[0016] The mass concentration of tetrapropylammonium hydroxide in the tetrapropylammonium hydroxide solution is (15-40) wt%;

[0017] The feed ratio of tetraethyl orthosilicate, metal zirconium salt, tetrapropylammonium hydroxide, potassium tetrachloroplatinate and distilled water in the tetrapropylammonium hydroxide solution is 1.0 mol: (0.0125-0.005) mol: (0.25-0.4) mol: (0.0006-0.0015) mol: (25-45) mol;

[0018] The feed ratio of the imidazole ionic liquid to potassium tetrachloroplatinate is (10-20) mol: 1.0 mol;

[0019] The drying temperature is 80-120°C and the drying time is 12-48 hours;

[0020] 3) The solid powder obtained in step 2) is transferred to a tube furnace, calcined in an air atmosphere, and then reduced in a hydrogen atmosphere to obtain the catalyst Pt@Zr-MFI, wherein:

[0021] The air flow rate is 50-100 mL / min, the calcination temperature is 400-700 °C, and the calcination time is 2-6 h;

[0022] The hydrogen flow rate is 50-100 mL / min, the calcination temperature is 150-400 °C, and the calcination time is 2-6 h;

[0023] The Pt loading is 0.1-0.5wt% of the catalyst mass;

[0024] The silicon-zirconium molar ratio of the Zr-MFI molecular sieve is in the range of 80 to 200;

[0025] The invention provides a method for preparing N-substituted-5-methylpyrrolidone from levulinic acid and an organic amine by using a zirconium-silicon molecular sieve encapsulated platinum sub-nano particle catalyst, which comprises the following steps:

[0026] 1) The above-mentioned Pt@Zr-MFI catalyst, levulinic acid and organic amine are placed in a stainless steel autoclave reactor lined with polytetrafluoroethylene. After the reactor is purged with high-purity nitrogen, high-purity hydrogen is filled into the reactor and maintained at a certain pressure, wherein:

[0027] The catalyst dosage is 0.02-0.06 g;

[0028] The molar ratio of the levulinic acid to the organic amine is (0.85-1.15) mol:1.0 mol;

[0029] The gas pressure is 0.1~2.0 MPa;

[0030] The organic amines are furfurylamine, aniline, 4-methoxyaniline, benzylamine, n-butylamine and cyclopentylamine;

[0031] 2) The pressure reactor is placed on a flat heater, heated to a preset temperature, and heated and stirred for a period of time to obtain the reaction product N-substituted-5-methylpyrrolidone. The reaction conversion rate and the yield of the target product are quantitatively measured by gas chromatography, wherein:

[0032] The preset temperature is 90-130 °C, the reaction time is 1-6 h, and the stirring rate is 800-1500 rpm / min;

[0033] The N-substituted-5-methylpyrrolidone is 1-furfuryl-5-methylpyrrolidone, 1-phenyl-5-methylpyrrolidone, 1-(4-methoxyphenyl)-5-methylpyrrolidone, 1-benzyl-5-methylpyrrolidone, 1-butyl-5-methylpyrrolidone and 1-cyclopentyl-5-methylpyrrolidone.

[0034] The present invention mainly solves the problems of easy loss of metal active species, poor thermal stability and low catalytic efficiency of traditional supported precious metal catalysts, and focuses on investigating the catalytic performance of the Pt@Zr-MFI catalyst of the present invention in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone. The main difficulty lies in how to integrate the hydrogenation active site and the Lewis acid site in the same molecular sieve catalyst to construct a precious metal-Lewis acid efficient synergistic catalytic system.

[0035] The zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst and its preparation method disclosed in the present invention have the positive effect compared with the prior art: the present invention utilizes the molecular sieve pore confinement effect to controllably synthesize Pt sub-nano particles, which can greatly improve the catalytic activity and utilization rate of the precious metal Pt and reduce the cost of catalyst use; the rigid structure of the molecular sieve framework can significantly enhance the stability and anti-sintering performance of the Pt sub-nano particles. The Pt@Zr-MFI catalyst provided by the present invention has both excellent catalytic hydrogenation performance and advanced Lewis acidity. In the application of preparing N-substituted-5-methylpyrrolidone with levulinic acid and organic amine as raw materials, it shows excellent catalytic activity and N-substituted-5-methylpyrrolidone yield. The catalyst structure is stable, and its catalytic activity does not show a significant decrease after multiple cycles of use. The catalyst preparation process is simple, the catalytic performance is excellent, the catalytic process cost is low and it is green and environmentally friendly, and it has important industrial application value in the field of pyrrolidone preparation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 TEM image of Pt@Zr-MFI catalyst;

[0037] Figure 2 XPS spectra of Pt@Zr-MFI catalyst (a) and sample treated with hydrofluoric acid (b);

[0038] Figure 3 is the XRD pattern of Pt@Zr-MFI catalyst;

[0039] Figure 4 This is the FTIR spectrum of pyridine adsorption of Pt@Zr-MFI catalyst. DETAILED DESCRIPTION

[0040] The present invention is described below by specific embodiments. Unless otherwise specified, the technical means used in the present invention are methods known to those skilled in the art. In addition, the embodiments should be understood as illustrative rather than limiting the scope of the present invention, and the essence and scope of the present invention are limited only by the claims. For those skilled in the art, various changes or modifications to the material components and dosages in these embodiments, without departing from the essence and scope of the present invention, also belong to the protection scope of the present invention. The specific experimental methods and equipment involved in the following examples are conventional methods or implemented according to the conditions recommended by the manufacturer's instructions unless otherwise specified. The reagents involved in the present invention are all commercially available and are used directly without purification.

[0041] The present invention is further described in detail and completely below in conjunction with specific embodiments.

[0042] Example 1

[0043] This example investigates the effect of different Pt contents on the catalytic performance of the Pt@Zr-MFI catalyst in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone.

[0044] The preparation method of the zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst comprises the following steps:

[0045] 1) At room temperature (25 °C), add 1-butyl-3-methylimidazolium bromide and distilled water into a beaker and stir until 1-butyl-3-methylimidazolium bromide is completely dissolved. Then, add potassium tetrachloroplatinate to the solution and continue stirring for 2 h. The prepared Pt precursor solution is ready for use.

[0046] The amount of 1-butyl-3-methylimidazolium bromide used is 0.223g;

[0047] The amount of distilled water is 3.6 mL;

[0048] The amount of potassium tetrachloroplatinate is 0.128g;

[0049] 2) Tetraethyl orthosilicate, zirconium oxychloride octahydrate and distilled water were added to the beaker in sequence, and after being fully stirred, tetrapropylammonium hydroxide solution was added dropwise, and stirring was continued for 4 hours until the tetraethyl orthosilicate was completely hydrolyzed. Then, the Pt precursor solution prepared in step 1) was added to the above sol, and after being mixed uniformly, it was transferred to a hydrothermal synthesis reactor and placed in an oven at 170 ° C for heating and crystallization for 3 days. After cooling to room temperature, the solid powder obtained by centrifugation was washed with a large amount of distilled water until it was neutral, and then dried in an oven at 120 ° C for 12 hours, wherein,

[0050] The amount of tetraethyl orthosilicate is 4.25 g;

[0051] The amount of zirconium oxychloride octahydrate is 0.043 g;

[0052] The amount of distilled water is 1.0 mL;

[0053] The tetrapropylammonium hydroxide solution is used in an amount of xx g and has a mass concentration of 15 wt %;

[0054] The amount of the Pt precursor solution is 9.49 g;

[0055] 3) The solid powder obtained by crystallization in step 2) is placed in a tube furnace, calcined in an air atmosphere to remove the template, and then calcined and reduced in a hydrogen atmosphere to obtain a Pt@Zr-MFI catalyst, wherein:

[0056] The solid powder dosage is 1.0 g;

[0057] The air flow rate is 50 mL / min, the calcination temperature is 550 °C, and the time is 6 h;

[0058] The hydrogen flow rate is 50 mL / min, the calcination temperature is 250 °C, and the calcination time is 4 h;

[0059] The Pt content in the Pt@Zr-MFI is 0.1-0.5wt% of the catalyst mass;

[0060] The silicon-zirconium molar ratio of the Zr-MFI molecular sieve is 150;

[0061] Figure 1 The instrument used is a Talos F200X transmission electron microscope produced by Thermo Fisher Scientific. The image in low-magnification mode (left) shows that the Pt@Zr-MFI molecular sieve has a regular crystalline appearance, which is a typical MFI crystal morphology. The crystal surface is clean and flat, and no amorphous products or large-scale aggregation of Pt particles are observed. In high-resolution HAADF-STEM mode (right), the lattice stripes of the MFI molecular sieve can be clearly identified, indicating that the skeleton structure of the MFI molecular sieve is not destroyed during the introduction of Pt sub-nanoparticles. In addition, it can be clearly observed that a large number of "bright spots" belonging to Pt sub-nanoparticles are evenly distributed inside the MFI crystals, and there is no obvious agglomeration phenomenon. This shows that the Pt sub-nanoparticles have been successfully encapsulated into the pores of the MFI molecular sieve. Figure 2The instrument used was a Kratos AXIS Ultra DLD X-ray photoelectron spectrometer produced by Kratos. In the XPS spectrum of Pt 4f, no signal peak related to Pt was detected on the surface of Pt@Zr-MFI molecular sieve (a). On the contrary, two photoelectron absorption peaks of zero-valent single substance Pt (binding energies of 74.7 and 71.3 eV, respectively) can be clearly observed in the sample treated with hydrofluoric acid (b), further indicating that the Pt sub-nanoparticles were successfully encapsulated into the pores inside the MFI molecular sieve crystals (JC Li, JM Li, Z. Zhao, XQ Fan, J. Liu,YC Wei, AJ Duan, Z. Xie, QL Liu, J. Catal .,2017, 352 , 361~370). Figure 3 The instrument used was a Bruker D8 X-ray powder diffractometer produced by Bruker. From the XRD results, it can be seen that the Pt@Zr-MFI molecular sieve exhibits a series of strong diffraction peaks, which are located at 2Ɵ= 7.9, 8.8, 23.1, 23.3, 23.8, 24.0 and 24.5 o These diffraction peaks are attributed to the characteristic diffraction peaks of MFI topology (ELWu, SL Lawton, DH Olson, AC Rohraman, GT Kokotailo, J. Phys. Chem. ,1979, 83 , 2777~2781), no diffraction peaks of large-particle Pt crystals were found, indicating that Pt sub-nanoparticles are highly dispersed inside the MFI crystals. Figure 4 The instrument used was a Bruker Tensor 27 infrared spectrometer produced by Bruker (equipped with a high-temperature reaction cell produced by Harrick Scientific). From the FT-IR spectrum of pyridine adsorption on Pt@Zr-MFI molecular sieve, it can be clearly observed that the 1611, 1490 and 1451 cm -1 Three absorption peaks, which are related to the pyridine molecules adsorbed on the Lewis acid sites (B. Tang, WLDai, XM Sun, GJ Wu, NJ Guan, M. Hunger, LD Li, Green Chem. ,2015, 17 , 1744~1755), even if the desorption temperature is increased to 300 ℃, these peaks still exist. This result shows that Pt@Zr-MFI molecular sieve has strong Lewis acidity.

[0062] The invention relates to the use of a zirconium-silicon molecular sieve encapsulated platinum sub-nano particle catalyst in the preparation of 1-furfuryl-5-methylpyrrolidone from levulinic acid and furfurylamine, comprising the following steps:

[0063] 1) Pt@Zr-MFI catalyst, levulinic acid and furfurylamine were added to a stainless steel autoclave lined with polytetrafluoroethylene, the reactor was purged with high-purity nitrogen for 5 times, and then high-purity hydrogen was filled into the reactor and maintained at 1.0 MPa, wherein,

[0064] The amount of the Pt@Zr-MFI catalyst is 0.04 g;

[0065] The amount of levulinic acid is 2.5 mmol;

[0066] The amount of furfurylamine is 2.5 mmol;

[0067] 2) placing the pressure reactor on a flat heater, heating it to 110°C, turning on the stirrer and maintaining the speed at 1000 rpm / min, reacting for 6 hours, cooling the reactor to room temperature, opening the vent valve to slowly release the remaining gas in the reactor, taking out the reaction liquid after opening the reactor, and analyzing the reaction using an Agilent 7890B gas chromatograph, wherein the gas chromatograph detector type is a FID detector;

[0068] The gas chromatograph column model is HP-5, with specifications of 30 m × 0.32 mm × 0.25 μm;

[0069] The catalytic performance results are shown in Table 1:

[0070] Table 1

[0071]

[0072] It can be seen from Example 1 that when the Pt content is 0.2wt%, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone are 24.6% and 24.1%, respectively. With the increase of the Pt content in the Pt@Zr-MFI catalyst, the conversion rate of levulinic acid and the yield of pyrrolidone increase accordingly. When the Pt content increases to 0.5wt%, the conversion rate of levulinic acid and the yield of pyrrolidone both reach the maximum value, which are 98.2% and 87.3%, respectively.

[0073] Example 2

[0074] This example investigates the effect of reaction temperature on the catalytic performance of Pt@Zr-MFI catalyst in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone, wherein the Pt content is 0.5 wt %, the reaction temperature is between 80 and 110° C., and other reaction conditions are the same as those described in Example 1. The catalytic performance evaluation results are shown in Table 2:

[0075] Table 2

[0076]

[0077] As shown in Example 2, when the reaction temperature is 90 °C, the Pt@Zr-MFI catalyst has excellent performance, and the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone are as high as 97.8% and 96.1%, respectively, which are better than the reaction performance at 80 °C (85.3%, 73.0%). With the further increase of the reaction temperature, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone only increase slightly.

[0078] Example 3

[0079] This example investigates the effect of reaction time on the catalytic performance of Pt@Zr-MFI catalyst in the conversion of levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone, wherein the Pt content is 0.5 wt %, the reaction time is between 1 and 6 h, and other reaction conditions are the same as those described in Example 1. The catalytic performance evaluation results are shown in Table 3:

[0080] Table 3

[0081]

[0082] It can be seen from Example 3 that when the reaction time is 1 h, the reaction activity of the Pt@Zr-MFI catalyst is low, and the conversion rates of levulinic acid and 1-furfuryl-5-methylpyrrolidone are only 25.1% and 12.6%. As the reaction time increases, the reaction activity of the Pt@Zr-MFI catalyst also increases. When the reaction time reaches 6 h, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone reach the maximum value (97.8% and 96.1%).

[0083] Example 4

[0084] This example investigates the effect of hydrogen pressure on the catalytic performance of Pt@Zr-MFI catalyst in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone, wherein the Pt content is 0.5 wt%, the hydrogen pressure is between 0.1 and 2.0 MPa, and other reaction conditions are the same as those described in Example 1. The catalytic performance evaluation results are shown in Table 4:

[0085] Table 4

[0086]

[0087] It can be seen from Example 4 that the performance of the Pt@Zr-MFI catalyst is closely related to the hydrogen pressure. When the hydrogen pressure is between 0.1 and 1.0 MPa, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone significantly increase with the increase of hydrogen pressure. When the hydrogen pressure is 1.0 MPa, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone reach 97.8% and 96.1%, respectively. However, when the pressure is further increased to 2.0 MPa, the conversion rate of levulinic acid and the yield of 1-furfuryl-5-methylpyrrolidone do not change significantly.

[0088] Example 5

[0089] This example investigates the effects of different imidazole ionic liquids on the catalytic performance of Pt@Zr-MFI catalyst in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone, wherein the Pt content is 0.5 wt %, the imidazole ionic liquids are 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide and 1-butyl-3-methylimidazolium bromide, and the other reaction conditions are the same as those described in Example 1. The catalytic performance evaluation results are shown in Table 5:

[0090] Table 5

[0091]

[0092] It can be seen from Example 5 that among the three ionic liquids of 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide and 1-butyl-3-methylimidazolium bromide, the Pt@Zr-MFI catalyst synthesized with 1-butyl-3-methylimidazolium bromide as a stabilizer has the best activity in the application of synthesizing 1-furfuryl-5-methylpyrrolidone from levulinic acid and furfurylamine, followed by 1-propyl-3-methylimidazolium bromide. In contrast, the Pt@Zr-MFI catalyst synthesized with 1-ethyl-3-methylimidazolium bromide as a stabilizer has a relatively low levulinic acid conversion rate and 1-furfuryl-5-methylpyrrolidone yield.

[0093] Example 6

[0094] This example investigates the recycling performance of the Pt@Zr-MFI catalyst in the reaction of converting levulinic acid and furfurylamine to prepare 1-furfuryl-5-methylpyrrolidone, wherein the Pt content is 0.5 wt %, and the other reaction conditions are the same as those described in Example 1. After the reaction, the reaction solution is centrifuged, and the solid sample obtained after centrifugation is washed 3 times with acetone, dried in an oven at 120 ° C for 2 h, and the dried sample is used for the next reaction. The catalytic performance evaluation results are shown in Table 6:

[0095] Table 6

[0096]

[0097] It can be seen from Example 6 that the catalytic activity of the Pt@Zr-MFI catalyst does not show a downward trend after at least 4 cycles of use. The evaluation results reflect the excellent structural stability and cyclic performance of the Pt@Zr-MFI catalyst of the present invention.

[0098] Example 7

[0099] This example investigates the use of Pt@Zr-MFI catalyst to catalyze the synthesis of different types of pyrrolidones from levulinic acid, wherein the Pt content is 0.5 wt %, and the other reaction conditions are basically the same as those in Example 1, except that the furfurylamine in Example 1 is replaced with aniline, 4-methoxyaniline, benzylamine, n-butylamine and cyclopentylamine in sequence, and the corresponding products are 1-phenyl-5-methylpyrrolidone, 1-(4-methoxyphenyl)-5-methylpyrrolidone, 1-benzyl-5-methylpyrrolidone, 1-butyl-5-methylpyrrolidone and 1-cyclopentyl-5-methylpyrrolidone. Catalytic performance evaluation is shown in Table 7:

[0100] Table 7

[0101]

[0102]

[0103] It can be seen from Example 7 that the Pt@Zr-MFI catalyst of the present invention has a wide range of substrate applications and can efficiently catalyze the synthesis of various types of N-substituted-5-methylpyrrolidone.

Claims

1. A method for preparing a platinum sub-nano particle catalyst encapsulated by a zirconium silicon molecular sieve, characterized in that Proceed as follows: 1) At room temperature of 20-25 °C, add a certain amount of imidazole ionic liquid and distilled water into a beaker, stir until the solution is clear, and then add potassium tetrachloroplatinate to the above solution for 1-2 h to obtain a Pt precursor solution; 2) Tetraethyl orthosilicate, metal zirconium salt and distilled water are mixed evenly, and tetrapropylammonium hydroxide solution is slowly added under stirring. After continuous stirring for 2 to 4 hours, the Pt precursor solution prepared in step 1) is added to the above sol. After the Pt precursor solution is completely mixed, the sol is transferred to a hydrothermal synthesis reactor, crystallized at 140 to 170 °C for 3 to 7 days, filtered, washed and dried to obtain a solid powder; In the above steps, the imidazole ionic liquid is 1-ethyl-3-methylimidazolium bromide, 1-propyl-3-methylimidazolium bromide or 1-butyl-3-methylimidazolium bromide; the feed ratio of the imidazole ionic liquid to potassium tetrachloroplatinate is (10-20) mol: 1.0 mol; The metal zirconium salt is zirconium tetrachloride, zirconium oxychloride octahydrate or zirconium oxynitrate; The mass concentration of tetrapropylammonium hydroxide in the tetrapropylammonium hydroxide solution is (15-40) wt%; The feed ratio of tetraethyl orthosilicate, metal zirconium salt, tetrapropylammonium hydroxide, potassium tetrachloroplatinate and distilled water in the tetrapropylammonium hydroxide solution is 1.0 mol: (0.0125-0.005) mol: (0.25-0.4) mol: (0.0006-0.0015) mol: (25-45) mol; The drying temperature is 80-120°C and the drying time is 12-48 hours; 3) The solid powder obtained in step 2) is transferred to a tube furnace, calcined in an air atmosphere, and then reduced in a hydrogen atmosphere to obtain the catalyst Pt@Zr-MFI, wherein: The air flow rate is 50-100 mL / min, the calcination temperature is 400-700 °C, and the calcination time is 2-6 h; The hydrogen flow rate is 50-100 mL / min, the calcination temperature is 150-400 °C, and the calcination time is 2-6 h; The Pt loading is 0.1-0.5wt% of the catalyst mass; The silicon-zirconium molar ratio of the Zr-MFI molecular sieve is in the range of 80 to 200; The chemical expression of the catalyst is Pt@Zr-MFI, wherein the Zr-MFI is a zirconium-containing zeolite molecular sieve having MFI topological structural characteristics, and the Pt is platinum sub-nanoparticles confined in the pores of the Zr-MFI molecular sieve.

2. Use of the zirconium silicon molecular sieve encapsulated platinum sub-nano particle catalyst prepared by the method of claim 1 in the preparation of N-substituted-5-methylpyrrolidone from levulinic acid and organic amine, wherein the application method is as follows: 1) The above-mentioned Pt@Zr-MFI catalyst, levulinic acid and organic amine are placed in a stainless steel autoclave reactor lined with polytetrafluoroethylene. After the reactor is purged with high-purity nitrogen, high-purity hydrogen is filled into the reactor and maintained at a certain pressure, wherein: The catalyst dosage is 0.02-0.06 g; The molar ratio of the levulinic acid to the organic amine is 0.85-1.15 mol:1.0 mol; The gas pressure is 0.1~2.0 MPa; The organic amine is furfurylamine, aniline, 4-methoxyaniline, benzylamine, n-butylamine or cyclopentylamine; 2) The pressure reactor is placed on a flat heater, heated to a preset temperature, and heated and stirred for a period of time to obtain the reaction product N-substituted-5-methylpyrrolidone. The reaction conversion rate and the yield of the target product are quantitatively measured by gas chromatography, wherein: The preset temperature is 90-130 °C, the reaction time is 1-6 h, and the stirring rate is 800-1500 rpm; The N-substituted-5-methylpyrrolidone is 1-furfuryl-5-methylpyrrolidone, 1-phenyl-5-methylpyrrolidone, 1-(4-methoxyphenyl)-5-methylpyrrolidone, 1-benzyl-5-methylpyrrolidone, 1-butyl-5-methylpyrrolidone or 1-cyclopentyl-5-methylpyrrolidone.